Problematika Guru dalam Implementasi Kurikulum Merdeka pada Pembelajaran IPAS Kelas IV MI Al Fithrah Surabaya - Ficky Dewi Ixfina (IBTIDAIYAH: Jurnal Penelitian dan Pendidikan Dasar Islam, 2025)
This study aims to describe the problems faced by teachers in implementing the Independent Curriculum  in IPAS learning at MI Al Fithrah Surabaya. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation, then analyzed thematically. The findings reveal three key issues: first, teachers’ understanding of the philosophical foundation of the Independent Curriculum remains limited to technical aspects without grasping its deeper meaning of “freedom to learn”; second, teachers’ pedagogical competence in integrating science and social studies, as well as in applying innovative learning models, remains underdeveloped; and third, institutional support and teachers’ adaptive strategies, including internal collaboration and the integration of tasawuf values, play a vital role in overcoming implementation barriers. This study concludes that the successful implementation of the Independent Curriculum requires a balance between philosophical understanding, pedagogical competence, and continuous institutional support.